The Correlation Between Stress Level and Premenstrual Syndrom Among College Students - Funsu Andiarna (State Islamic University of Sunan Ampel, 2018)
Among health disorders in women who were difficult to identify was a set of symptoms known as premenstrual syndrome. Approximately 80%-95% of women between the ages of 16 to 45 years experiencing an annoying premenstrual syndrome symptoms. Premenstrual syndrome can be triggered by several factors, mainly caused by stress. The purpose of this research was to investigated the correlation between the stress level with the incidence of premenstrual syndrome among college student. This was an observational analytical research with cross sectional approach. The research was conducted at State Islamic University Sunan Ampel Surabaya with 35 respondents acted as a research samples. The study used Chi-Square tes for bivariat analysis. The result showed that there was a meaningful correlation between the stress level with premenstrual syndrome (p = 0.040), confirming the stress variable as one of the factors that can lead to the occurrence of premenstrual syndrome. From this research concluded that the stress level must be well managed by the female college students so the incidence of premenstrual syndrome can be prevented.